State of the Art in Biosensors Environmental and Medical Applications - Rinken, Toonika (IntechOpen, 2013)
The main challenge in biosensor development is their application for various practical tasks to provide a continuous and reliable flow of information about the indicators of natural and industrial processes and the surroundings, so enabling adequate feedback and control. Biosensors can provide essential information, as the quality of life depends mainly on our knowledge about what we breathe, what we eat and how our bodies are able to metabolize the material, which we contact. This book includes 14 chapters, written by 52 authors and is focused on the applications of biosensors for monitoring the parameters of environment, the quality of food and biomarkers of health.